Improving bread-making processing phases of fibre-rich formulas using chia (Salvia hispanica) seed flour. (October 2017) - Verdú, Samuel; Barat, José M.; Grau, Raúl
Abstract: The capacity of chia seed flour to improve the behaviour of wholemeal formulas of wheat bread during the bread-making process was tested. Seven formulas were produced: one employing only wheat flour (control), two formulas substituting 13% and 23% (d.b.) of wheat flour with bran (wholemeal), and these last two bran formulas were combined in turn with chia, in which substituting 5% and 10% (d.b.) of their wheat flour fraction. The fermentation phase improved. Chia led to an increase in the gas retention of dough with 13% of bran, and height was reached with no differences compared to the refined wheat dough. Water retention did not show differences between formulas after the baking phase. The 13% bran/5% chia formula generated breads with 12% fibre content (w.b), but no differences were found in specific volume and similar hardness to the refined wheat ones. Finally, this bran/chia combination, which showed no differences during the bread-making process with the refined wheat formula, was tested for sensory attributes. No significant effect was detected on the sensory attributes compared to the same wholemeal formula without chia flour. Chia modified the properties of wholemeal doughs, which improved the bread making process and produced bread with no deterioration in sensory attributes. Highlights: The capacity of chia to improve the bread-making process of wholemeal dough was tested. Wheat flour was partially replaced with combinations of bran/chia to obtain the studied formulas. Fermentation and bread features improved significantly with chia incorporation. Chia improved bread-making process of dough without affecting bread sensory attributes.